Yoga May Mitigate Decreases in High School Grades. (10th August 2015) - Butzer, Bethany; van Over, Max; Noggle Taylor, Jessica J.; Khalsa, Sat Bir S.
Abstract : This study involves an exploratory examination of the effects of a 12-week school-based yoga intervention on changes in grade point average (GPA) in 9th and 10th grade students. Participants included 95 high school students who had registered for physical education (PE) in spring 2010. PE class sections were group randomized to receive either a yoga intervention or a PE-as-usual control condition. The yoga intervention took place during the entire third quarter and half of the fourth quarter of the school year, and quarterly GPA was collected via school records at the end of the school year. Results revealed a significant interaction between group and quarter suggesting that GPA differed between the yoga and control groups over time. Post hoc tests revealed that while both groups exhibited a general decline in GPA over the school year, the control group exhibited a significantly greater decline in GPA from quarter 1 to quarter 3 than the yoga group. Both groups showed equivalent declines in GPA in quarter 4 after the yoga intervention had ended. The results suggest that yoga may have a protective effect on academic performance by preventing declines in GPA; however these preventive effects may not persist once yoga practice is discontinued.